The Evolving Role of Emergency Departments in the United States - Gonzalez Morganti, Kristy (RAND Corporation, 2013)
This report explores the evolving role that hospital emergency departments play in the U.S. health care system. EDs evaluate and manage complex and high-acuity patients, are the major point of entry to inpatient care, and serve as "the safety net of the safety net" for patients who cannot get care elsewhere. The report examines the role that EDs may come to play in either contributing to or reducing the rising costs of health care.